Synthesis and utilization of platinum(II) dialkyldithiocarbamate precursors in aerosol assisted chemical vapor deposition of platinum thin films as counter electrodes for dye-sensitized solar cells. (1st July 2019) - Ehsan, Muhammad Ali; Younas, Muhammad; Rehman, Abdul; Altaf, Muhammad; Khan, Mohd. Yusuf; Al-Ahmed, Amir; Ahmad, Saeed; Isab, Anvarhusein A.
Graphical abstract: Newly synthesized dithiocarbamate precursors of platinum are used in a facile one-step AACVD procedure to fabricate pure phase platinum thin films of deposition time dependent structural and dimensional attributes. These films have shown higher efficiency as counter electrodes in dye sensitized solar cells as compared to the configurations using platinum electrodes made via doctor blade's method. Abstract: A facile and cost effective AACVD procedure for the synthesis of platinum thin films has been reported using newly synthesized Pt-dialkyldithiocarbamate complexes, [Pt(S2 CNR2 )] (where R = isobutyl, i Bu (1 ); benzyl, Bz (2 )), as single source precursors. The structural characterization of the dithiocarbamate complexes has been performed by single crystal X-ray diffraction, 1 H and 13 C NMR, FT-IR and thermogravimetric analysis. The structure, composition, and morphology of the resulting Pt-films is established through XRD, XPS, EDX and FE-SEM analyses. The catalytic performance of the as-synthesized Pt-films is evaluated by using them as counter electrodes in dye sensitized solar cells as an example application. The efficiency of the AACVD produced electrodes is found to be better than conventionally used Pt-counter electrodes made from the doctor blade's method. It is also demonstrated that films having a well-connected and defect free surface topography show better catalytic performance, which is due to their high conductivity and reflectivity. Thus a simple and low cost method employing dithiocarbamate precursors is manifested to be immensely efficient in generating Pt-films and electrodes of tremendous applicability.